Traços desejantes da cidade: o apelo pela modernização em São Luís (1889 1970) - Silva, Gabriela Melo (2012)
This essay has got the goal to study the modernization of the urban environment from the interventions done by public power. This kind of interventions are the changes made on architecture and infrastructure -water channeling, sewer systems, electric power, streets and avenues (construction)-. The chosen place for this research is Sao Luís Northeastern Brazil, Maranhão State capital city- from 1889 to 1970. Sao Luis had a late insertion in the capitals market. It was when Brazil was still a Portuguese cologne, not so modern like another countries. It was necessary to exert despotism in Lusitanian lands for an economic structuring finally to appear and the city s scenery could be changed. This growth led to the first modernization of the urban environmental movement. The building of some sobrados two-floor houses- and sidewalks was given then. In the second half of XIX century the economic prosperity led to decadence and a pessimist feeling. At the same time the republican regime is established in the country. This situation provoked the need to forget all those issues related to monarchy. In this way and following the positivist patrons, modernization appeared as a way of transformation. Not only Republic caused this feeling. Changes were given fast in the West. New habitus sprang up and spread quickly. In opposition to some theoreticians thought, modernization did not die out through the years. It was gaining new shapes and necessities. As a matter of fact, modernization appears nowadays in political speeches and practices as the most important way to development. In a first moment, we divided the modernization process of Maranhão capital in three stages but then, having carried our survey out we realized that this did not longer was didactic. Nevertheless, it became more real and necessary. Sao Luís modernization process has got three stages of transformation. The first stage starts in 1889 when laws begin to be more focused in urban environment, organization and beauty and finishes in the late 20 s. The second stage starts in the 30 s and finishes in the late 40 s, when the state begins to interfere with the whole nation. The state then, starts a urban-industrial project. Finally, in the 60 s and 70 s great infrastructure construction works are done in Maranhão capital city, i.e. the bridge on the Anil River, the dam on the Bacanga River and Itaqui Port. These construction works define a style. To conclude, this modernization is established as a public policy or a group of public policies. It is necessary interventions to carry out these policies, which may be structural and / or related to social control.